PERSPEKTIF HAK ASASI MANUSIA TERHADAP PENYALAHGUNAAN DEEPFAKE ATAS HAK PRIVASI SESEORANG - Putu Clarissa Taramitha Devi; I Made Wirya Darma; Ni Gusti Agung Ayu Mas Tri Wulandari; Bagus Gede Ari Rama (Berajah Journal, 2026)
The rapid advancement of Artificial Intelligence (AI) has given rise to new forms of cybercrime, one of which is deepfake technology. Deepfakes involve the manipulation of videos, audio, or images to create fabricated content that may harm the dignity, reputation, and privacy of individuals. This study addresses two research questions: (1) What is the legal responsibility of perpetrators who misuse deepfake technology in ways that violate an individual's right to privacy under the Indonesian legal system? and (2) How are the human rights of victims of deepfake misuse that infringes upon the right to privacy protected? The objectives of this study are, first, to examine the enforcement of laws against perpetrators of deepfake pornography in Indonesia and, second, to analyze the legal protection available to victims of deepfake misuse from a human rights perspective. This research employs a normative legal research method based on library research, utilizing statutory regulations, books, scholarly journals, and other relevant legal sources. The findings indicate that individuals who create and disseminate deepfake content that violates another person's right to privacy must be held legally accountable for their actions. Furthermore, victims of deepfake misuse are entitled to legal protection grounded in the principles of human rights.